2021
DOI: 10.1007/s43440-021-00234-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and control of steroid-induced hyperglycaemia in hospitalised patients at a tertiary care centre for lung diseases

Abstract: Background The aim of this study was to determine the incidence of steroid-induced hyperglycaemia (SIH) in patients hospitalised at the tertiary centre for lung diseases, to assess glycaemic control during hospitalisation, and to determine the factors associated with the control of SIH. Methods A 4-month retrospective study was conducted. All patients who received systemic glucocorticoids for ≥ 2 days during hospitalisation, with ≥ 2 elevated blood glucose (BG) readings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
1
0
2
Order By: Relevance
“…Среди наших пациенток сахарного диабета выявлено не было; но в 24,8 % случаев зарегистрирована гипергликемия на фоне терапии ГК, при отмене препаратов уровень глюкозы нормализовался. По данным различных источников, гипергликемия при COVID-19 встречается в 20-70 % случаев [22,23].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Среди наших пациенток сахарного диабета выявлено не было; но в 24,8 % случаев зарегистрирована гипергликемия на фоне терапии ГК, при отмене препаратов уровень глюкозы нормализовался. По данным различных источников, гипергликемия при COVID-19 встречается в 20-70 % случаев [22,23].…”
Section: Discussionunclassified
“…Имеющиеся на сегодняшний день данные не позволяют достоверно оценить влияние COVID-19 на материнскую смертность в популяции в целом. К настоящему времени показатели материнской смертности за 2020 г. представили около 20 % стран, в которых нерепрезентативно высока доля обеспеченных и / или сравнительно небольших групп населения, что ограничивает возможность экстраполяции оценок на генеральную совокупность [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionunclassified
“…Multivariate analysis was performed using logistic regression to evaluate the effects of PBW-based dexamethasone therapy on the risk of additional insulin therapy. A previous study showed that age, body mass index, history of diabetes mellitus, and duration of steroid therapy were the risk factors for insulin therapy; therefore, we used these same parameters in our analysis [ 18 ]. Two-tailed P-values < 0.05 were considered significant.…”
Section: Methodsmentioning
confidence: 99%